CAPACIDADES ESTATAIS PARA POLÍTICA DE TURISMO NO POLO COSTA BRANCA - RN / STATE CAPACITIES FOR TOURISM POLICY AT THE WHITE COAST REGION - RN - Miranda Júnior, Lírio Martins de; Magalhães da Silva, Ângelo Magalhães da Silva (Informe GEPEC, 2023)
Resumo: Este artigo tem como objetivo analisar as capacidades estatais para a política de turismo nos municípios do Polo Costa Branca. Para isso, se apoiou em uma pesquisa bibliográfica e documental sobre Programa de Regionalização do Turismo, consubstanciada por uma revisão teórica sobre capacidades estatais e a aplicação de modelo analítico voltado investigação dos arranjos institucionais, realizada por meio de pesquisa de campo, composta pela aplicação de questionários e entrevistas junto aos órgãos públicos responsáveis pela política de turismo nos seis municípios que compõem a região. A análise dos resultados revelou a precarização de elementos da capacidade estatal dos municípios, que comprometem a atuação destes nos processos de descentralização e territorialização da política de turismo. Abstract: This article aims to analyze the state's capabilities for tourism policy in the municipalities of the White Coast Region o. To do so, it relied on a bibliographic and documentary research on the Tourism Regionalization Program, substantiated by a theoretical review of state capabilities and the application of the analytical model aimed at investigating institutional arrangements, carried out through field research, consisting of the application of questionnaires and interviews with the public bodies responsible for tourism policy in the six municipalities that make up the region. The analysis of the results revealed the precariousness of elements of the state capacity of the municipalities, which compromise their performance in the processes of decentralization and territorialization of the tourism policy